Study of Asphervon Gum Effect on Diuresis, Spermatogenesis and Its Effect on Testosterone Level in Rat Male Blood - Samedinov Rustem Selyametovich; Nabiev Abduvali Nabievich; Tulyaganov Sattar Khakimovich (Indian Journal of Forensic Medicine & Toxicology, 2022)
The effect of Asphervon resin gum on spermatogenesis, on the level of testosterone in the blood of rats was studied, and the effect of two dosages of the drug on diuresis of rats with an aqueous load was also considered. Data have been obtained on the quantitative change of sperm in the rat ejaculate, on the ability of Asfervon to reduce testosterone levels in the rat’s blood, and also, a pronounced dose has been revealed - the dependent diuretic effect of the drug Asfervon.